2004
DOI: 10.1103/physrevlett.92.117002
|View full text |Cite
|
Sign up to set email alerts
|

Critical Currents at the Bragg Glass to Vortex Glass Transition

Abstract: We present simulations of the transport properties of superconductors at the transition from the Bragg glass (BG) to the vortex glass (VG) phase. We study the frustrated anisotropic 3D XY model with point disorder, which has been shown to have a first order transition as a function of the intensity of disorder. We add an external current to the model and we obtain current-voltage curves as a function of disorder at a low temperature. We find that the in-plane critical current has a steep increase at the BG-VG … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this work, a first order transition separates the moving 3D ordered state from a moving smectic state, which transitions continuously into a liquid state as a function of temperature. Hernández and Domínguez studied a similar model and observed that a first order transition from a 3D ordered pinned state to a 2D disordered state is associated with a large increase in the depinning threshold [125].…”
Section: Depinning and Dynamical Phase Transitionsmentioning
confidence: 97%
“…In this work, a first order transition separates the moving 3D ordered state from a moving smectic state, which transitions continuously into a liquid state as a function of temperature. Hernández and Domínguez studied a similar model and observed that a first order transition from a 3D ordered pinned state to a 2D disordered state is associated with a large increase in the depinning threshold [125].…”
Section: Depinning and Dynamical Phase Transitionsmentioning
confidence: 97%
“…For example, in model random field systems near a phase transition, critical thermal fluctuations dominate until the length scale of the order parameter becomes large enough where static terms originating from the induced disorder dominate 19,20 . Examples of new disordered-induced phases include the concept of "Bragg glass" [21][22][23][24][25] that were first postulated in the context of flux lattices in superconductors [26][27][28] where Bragg peaks exist, however other properties reflect a glass type response. A further example of unusual phases in the presence of disorder is the Griffiths phase [29][30][31] that was first suggested in the context of Ising ferromagnets, where an ordered local region co-exists within a globally disordered phase.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the vortex state in high temperature superconductors (HTSCs) has been extensively debated in recent years [1][2][3][4][5][6][7][8][9][10]. The solid-to-liquid phase transition is most probably a first order melting transition in very clean systems, but turns into a second order vortex glass transition for highly disordered systems involving point defects or a Bose glass transition in systems with corrected defects like ion-induced columnar defects or twin boundaries [11].…”
Section: Introductionmentioning
confidence: 99%